PENGARUH PEMANFAATAN PERPUSTAKAAN DIGITALTERHADAP PRESTASI AKADEMIK SISWA MADRASAH ALIYAH NEGERI 3 PEKANBARU - Rahmadanni Pohan; Muhammad Rafi; Yuliana Yuliana (Elementary School and Education Journal, 2026)
Pekanbaru State Islamic Senior High School 3 is a state Islamic senior high school located in Pekanbaru, Riau, and was inaugurated by the Minister of Religious Affairs of the Republic of Indonesia on October 29, 2018. The library of Pekanbaru State Islamic Senior High School 3 has implemented a digital library system. The purpose of this study was to determine the significant influence of digital library utilization on student academic achievement at Pekanbaru State Islamic Senior High School 3. The data collection technique used in this study was a survey design, observation, and questionnaires. This study employed quantitative methods with descriptive analysis based on the data obtained to answer the hypothesis of the influence of digital library utilization on student academic achievement. The analysis and conclusions showed that both variables were in the very strong or very high category, at 0.989, with a coefficient of determination (RS-square) of 0.977%. The contribution of digital library utilization to the academic achievement of students at Madrasah Aliyah 3 Pekanbaru is 97.7%, with the remainder determined by other variables. Digital library utilization can also predict future student academic achievement.